Poly I:C Activated Microglia Disrupt Perineuronal Nets and Modulate Synaptic Balance in Primary Hippocampal Neurons in vitro - Wegrzyn, David; Freund, Nadja; Faissner, Andreas; Juckel, Georg (Frontiers in Synaptic Neuroscience, 2021)
Perineuronal nets (PNNs) are specialized, reticular structures of the extracellular matrix (ECM) that can be found covering the soma and proximal dendrites of a neuronal subpopulation. Recent studies have shown that PNNs can highly influence synaptic plasticity and are disrupted in different neuropsychiatric disorders like schizophrenia. Interestingly, there is a growing evidence that microglia can promote the loss of PNNs and contribute to neuropsychiatric disorders. Based on this knowledge, we analyzed the impact of activated microglia on hippocampal neuronal networks in vitro. Therefore, primary cortical microglia were cultured and stimulated via polyinosinic-polycytidylic acid (Poly I:C; 50 µg/ml) administration. The Poly I:C treatment induced the expression and secretion of different cytokines belonging to the CCL- and CXCL-motif chemokine family as well as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). In addition, the expression of matrix metalloproteinases (MMPs) could be verified via RT-PCR analysis. Embryonic hippocampal neurons were then cultured for 12 days in vitro (DIV) and treated for 24 h with microglial conditioned medium. Interestingly, immunocytochemical staining of the PNN component Aggrecan revealed a clear disruption of PNNs accompanied by a significant increase of glutamatergic and a decrease of γ-aminobutyric acid-(GABA)ergic synapse numbers on PNN wearing neurons. In contrast, PNN negative neurons showed a significant reduction in both, glutamatergic and GABAergic synapses. Electrophysiological recordings were performed via multielectrode array (MEA) technology and unraveled a significantly increased spontaneous network activity that sustained also 24 h and 48 h after the administration of microglia conditioned medium. Taken together, we could observe a strong impact of microglial secreted factors on PNN integrity, synaptic plasticity and electrophysiological properties of cultured neurons. Our observations might enhance the understanding of neuron-microglia interactions considering the ECM.